Woorden en de beelden (de) : tekst en beeld in de kunst van de twintigste eeuw. - Broos, K. (Utrecht : Centraal Museum, 1991)
Apollinaire, Guillaume ; Baldessari, John ; Ball, Hugo ; Balla, Giacomo ; Barry, Robert ; Basquiat, Jean-Michel ; Baumgarten, Lothar ; Baxter, Glen ; Belloli, Carlo ; Beuys, Joseph ; Borofsky, Jonathan ; Braque, Georges ; Breton, André ; Broodthaers, Marcel ; de Campos, Haroldo ; Cangiullo, Francesco ; Carrà, Carlo ; Charchoune, Serge ; Chopin, Henri ; Crotti, Jean ; Daniels, René ; Depero, Fortunato ; Desnos, Robert ; Diamond, Jessica ; van Doesburg, Theo ; Dokoupil, Jiri Georg ; Duchamp, Marcel ; Dumas, Marlene ; Dwyer, Nancy ; Ernst, Max ; Gomringer, Eugen ; Gontscharowa, Natalia ; Gudmundsson, Sigurdur ; Finlay, Ian Hamilton ; Hausmann, Raoul ; Höch, Hannah ; Holzer, Jenny ; Huber, Thomas ; Immendorff, Jörg ; Indiana, Robert ; Jenney, Neil ; Johns, Jasper ; Kok, Antony ; Kruger, Barbara ; Larionov, Michail ; Lissitzky, El ; Lum, Ken ; Mac Low, Jackson ; Magritte, René ; Malevich, Kasimir ; Marinetti, Filippo Tommaso ; Masson, Andre ; Mayer, Hans-Jörg ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mol, Pieter Laurens ; Mondriaan, Piet ; Nauman, Bruce ; Penck, A.R. ; Picabia, Francis ; Picasso, Pablo ; Polke, Sigmar ; Prince, Richard ; Rollins, Tim & K.O.S. ; de Rook, Gerrit Jan ; Roth, Dieter ; Ruscha, Edward ; Schwitters, Kurt ; Seuphor, Michel ; Severini, Gino ; Spero, Nancy ; Twombly, Cy ; Tzara, Tristan ; Weiner, Lawrence ; Werkman, Hendrik Nicolaas
boek
Keywords: Broos, Kees